The metastable states of proteins. (11th April 2020) - Ghosh, Debasish Kumar; Ranjan, Akash
Abstract: The intriguing process of protein folding comprises discrete steps that stabilize the protein molecules in different conformations. The metastable state of protein is represented by specific conformational characteristics, which place the protein in a local free energy minimum state of the energy landscape. The native‐to‐metastable structural transitions are governed by transient or long‐lived thermodynamic and kinetic fluctuations of the intrinsic interactions of the protein molecules. Depiction of the structural and functional properties of metastable proteins is not only required to understand the complexity of folding patterns but also to comprehend the mechanisms of anomalous aggregation of different proteins. In this article, we review the properties of metastable proteins in context of their stability and capability of undergoing atypical aggregation in physiological conditions.